2016
DOI: 10.1039/c6an01073c
|View full text |Cite
|
Sign up to set email alerts
|

An optimised assay for quantitative, high-throughput analysis of polysialyltransferase activity

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…We conclude that CMP‐Neu5Cyclo binds to the donor binding site of ST8SiaII, thus directly competing with CMP‐Sia. The level of inhibition is comparable to that observed for CMP, thus indicating that Neu5Cyclo does not make a strong contribution to binding affinity. However, as this substrate is unable to be transferred to polySia, it serves as a useful lead compound in the search for new anticancer therapeutics.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…We conclude that CMP‐Neu5Cyclo binds to the donor binding site of ST8SiaII, thus directly competing with CMP‐Sia. The level of inhibition is comparable to that observed for CMP, thus indicating that Neu5Cyclo does not make a strong contribution to binding affinity. However, as this substrate is unable to be transferred to polySia, it serves as a useful lead compound in the search for new anticancer therapeutics.…”
Section: Resultssupporting
confidence: 64%
“…For investigating the preference for specific acceptor structures, it was essential to measure only the first transfer onto the acceptor, as each transfer generated a new acceptor species with potentially different acceptor properties. We applied optimised reaction conditions for predominantly single transfers, thus obtaining DMB‐DP4 and DMB‐DP13 as the major products . Preliminary tests using equal amounts of the two polySTs showed that the specific activity of ST8SiaIV was considerably lower than that of ST8SiaII.…”
Section: Resultsmentioning
confidence: 99%
“…DMB-DP3 synthesis was conducted as described previously. 20 Briefly, DP3 (10 mg ml −1 ) was dissolved in a labelling solution containing DMB (20 mM), sodium hydrosulfite (40 mM) and β-mercaptoethanol (1 M). The mixture was then added to an equal volume of ice-cold trifluoroacetic acid (40 mM), followed by incubation at 4°C overnight.…”
Section: Dmb-dp3 Synthesis and Purificationmentioning
confidence: 99%
“…1). 20 The fluorescent acceptor and product in the enzyme reaction are separated by reversed-phase chromatography over a short timeframe (10 min), while being simultaneously visualised by fluorescence detection (Fig. 1, inset), allowing rapid analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation